The use of cassava leaf silage for feeding growing pigs and sows in Central Vietnam - Nguyen, Thi Hoa Ly; Nguyen, Thi Loc; Du, Thanh Hang; Le, Van An (International Center for Tropical Agriculture, 2001)
This study aimed at using cassava leaves, ensiled with rice bran, sugar molasses and cassava root meal (at 5 and 10% levels), as a protein source for growing pigs and pregnant Mong Cai sows. The added ingredients contributed to producing good quality silage (pH 3.8 or less; HCN 90- 120 mg/kg fresh silage) which could be stored for up to five months. Digestibility and nitrogen balance trials were conducted to evaluate the substitution of fish meal by ensiled cassava leaves (ECL) at the levels of 0, 50, 75 and 100 g/day of protein in diets based on ensiled cassava roots (ECR). There was an indication (P = 0.08) that apparent digestibility of the dry matter (DM) decreased with increasing levels of ECL. The decrease in crude protein (CP) digestibility, from 86.6 to 79.6 for 100 g/day substitution, was highly significant (P = 0.001). Nitrogen retention also decreased from 14.5 to 9.0 g/day when ECL was used at the level of 100 g/day of protein. The inclusion of 10% ensiled cassava leaves as replacement for sweetpotato vines and partial replacement for fishmeal in growing Mong Cai gilt had no effect on reproductive performance. However, at the 20% level, the live weight gain of gilts was decreased, age at first mating was increased from 170 to 196 days, and live weight increased from 40.2 to 43.8 kg. Twenty-four crossbred pigs (Mong Cai x Large White) were allocated (4 pigs/household) among two groups of families to compare the effect of supplementing the traditional diet with ensiled cassava leaves. The overall difference was not significant and no effect on the growth of pigs was observed. In another 16 households, feeding of 15% ensiled cassava leaves to Mong Cai sows during pregnancy, as replacement for sweetpotato vines and partial replacement of fishmeal, had no effect on reproductive traits.